Pacing behavior and tactical positioning in 500- and 1000-m Short-Track Speed Skating - Noorbergen, O. S.; Konings, M. J.; Micklewright, D.; Elferink-Gemser, M. T.; Hettinga, F. J. (International Journal of Sports Physiology and Performance, 2016)
Purpose: